Secure exams question management system based on blockchain technology / Muhammad Zarif Ikhmal Ahmad Nazri - Ahmad Nazri, Muhammad Zarif Ikhmal (2019)
The Secure Exams Question Management System (SEQM) is a web application that operates on peer-to-peer networks and are based on the emerging blockchain technology. This web application was developed for the Universiti Teknologi Mara (UiTM) staff to securely upload and store examination question. Blockchain is utilize once the file hash has been upload to InterPlanetary File System (IPFS) and store the hash that were generated from it inside the Ethereum Blockchain. The users are also able to share the file hash with each other. The benefits of using this system are that there is no centre point of failure such as database breaches or the server is busy. Furthermore, in term of security, once the file has been upload, no one’s could temper with the file hash, as it is store inside the blockchain.